Aspek Hukum Non-Competition Clause dalam Perjanjian Kerja - Arif Fajri Alkad; Edith Ratna Mulyaningrum (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Every company needs an employee as a worker to carry out all the company's business activities. Employees are important assets of the company. In the employment agreement there is one legal aspect that is detrimental to the employee. The aim to be achieved in this research is to find out about the purpose of making a Non Competition Clause by the company in a work agreement whether it is contrary to the laws and regulations and how the legal protection will be for a non competition clause. The research method used is a normative research method by conducting a research approach used is a statutory and conceptual approach. Conclusions from the research: 1) The non-competition clause in the work agreement is contrary to Law Number 13 of 2003 concerning Manpower and the Civil Code, in the Civil Code the non-competition clause is regulated for its implementation but does not use the term clause or competition. Meanwhile, according to the Manpower Act, every worker has the right and opportunity to choose, get or move to a decent job. 2) Legal protection for workers/laborers with the existence of a Non Competition Clause, the 1945 Constitution of the Republic of Indonesia emphasizes that the protection of human rights is the responsibility of the state, especially the government. people have the right to freely choose the work they like and are also entitled to fair employment conditions. Every company needs an employee as a worker to carry out all the company's business activities. Employees are important assets of the company. In the employment agreement there is one legal aspect that is detrimental to the employee. The aim to be achieved in this research is to find out about the purpose of making a Non Competition Clause by the company in a work agreement whether it is contrary to the laws and regulations and how the legal protection will be for a non competition clause. The research method used is a normative research method by conducting a research approach used is a statutory and conceptual approach. Conclusions from the research: 1) The non-competition clause in the work agreement is contrary to Law Number 13 of 2003 concerning Manpower and the Civil Code, in the Civil Code the non-competition clause is regulated for its implementation but does not use the term clause or competition. Meanwhile, according to the Manpower Act, every worker has the right and opportunity to choose, get or move to a decent job. 2) Legal protection for workers/laborers with the existence of a Non Competition Clause, the 1945 Constitution of the Republic of Indonesia emphasizes that the protection of human rights is the responsibility of the state, especially the government. people have the right to freely choose the work they like and are also entitled to fair terms of employment.